Analysis of Kulin KK LMDH Sumber Lestari Based Agroforestry Social Partnership Program in BKPH Tulungagung - Mardiani Dian; Ahsin Daroini; Supriyono (Agricultural Science, 2021)
Forest Village Community Institution (LMDH) "Sumber Lestari" was formed after the emergence of the Community Forest Management (PHBM) program in 2004. Geographically, samar village is a forest stakeholder village and nearly 45% of Samar village is a state forest area. The research objectives are; 1) Analyze the extent to which the Forestry Partnership Program (Kulin KK) LMDH Sumber Lestari is implemented in the Agroforestry-based social forestry program scheme at BKPH Tulungagung. 2) Analyze the economic benefits felt by Perum Perhutani and the surrounding community (LMDH) by implementing the LMDH Sumber Lestari Forestry Partnership Program (Kulin KK) in the Agroforestry-based social forestry program scheme at BKPH Tulungagung. The research method used is descriptive analysis. Descriptive analysis is used to describe the characteristics of the research area, the characteristics of the respondents, the socio-economic characteristics of the community, the analysis of forestry partnerships. The research results are as follows; From the pine stand commodity (sadapan), the income was Rp. 5,061,600,000, coffee Rp. 23,625,000, commodity porang Rp. 25,300,000,000, commodity empon-empon Rp. 62,764,000,000, and Rp. total revenue was 94,873,377,500. Of the total income, there is no profit sharing with Perum Perhutani KPH Kediri, with provisions for stand management (tapping pine), distribution is carried out at a ratio of 75: 25 where 75% of Perum Perhutani KPH Kediri, while 25% is owned by LMDH Sumber Lestari farmers. As for agroforestry commodities, the ratio is divided into 70: 30 with a record that 70% of LMDH Sumber Lestari farmers and 30% are Perum Perhutani KPH Kediri.